Hamka and the Rise of Kaum Muda (the Modernist) in Indonesia - Ahmad Nabil Amir; Tasnim Abdul Rahman (Universitas Muhammadiyah Malang, 2024)
The paper aims to study the historical background of the Islamic reform movement in West Sumatra with particular reference to the idea of Haji Abdul Malik Karim Amrullah or his pseudonym Hamka (1908-1981). His religious ideal was instrumental in driving the new consciousness and unprecedented religious struggle that erupted in the late 20th century in the Malay Archipelago, which reflected the force of modern ideas of Shaykh Muhammad Abduh (1849-1905) that had brought decisive and greatest influence in the region. The reform movement he inaugurated was carried out by Kaum Muda (the young faction) in the Malay Archipelago, who disseminated his dynamics ideas and aspirations through journals and newspapers such as Al-Imam, Al-Munir, and Saudara. One of the leading figures and pioneers in the struggle of Kaum Muda was Haji Rasul dan Kiyai Ahmad Dahlan, whose legacy was continued by Hamka, who was hailed as the foremost advocate of Abduh’s reformist ideas through his influential writing and activity. To highlight this significant work and idealism, this research presents and analyzes Hamka’s struggle to lead this unprecedented religious movement for reform (islah) and renewal (tajdid) in the Malay world. This research aims to develop his legacy and monumental contribution to the history and tradition of reform in the Malay world.